West nile virus in Portugal: vector population, host interaction and detection of new flaviviruses - Osório, Hugo Costa (2013)
This thesis describes the studies undertaken in the epidemiology of West Nile virus (WNV) in Portugal exploring several key components of its natural cycle: identification of mosquito vector-populations – geographical and seasonal distribution; analysis of genetic and environmental determinants on feeding patterns of mosquito vectors; experimental transmission of WNV; identification of flaviviruses detected in wild mosquitoes; serological survey of wild birds potentially involved in the epizootic cycle of WNV; finally, a description of a clinical human case of WNV infection reported in 2010. Culex pipiens was one of the most abundant mosquito species demonstrating ecological and intrinsic competence to transmit WNV. No positive mosquito pools for WNV were detected, but new mosquito-only flaviviruses were identified. The presence of antibodies anti-WNV in a juvenile turtle-dove suggests local virus circulation. In conclusion, Portugal meets suitable conditions for epizootic circulation of WNV and for the occurrence of accidental human infections; RESUMO O vírus West Nile em Portugal Vetores, interação com hospedeiros e deteção de novos flavivírus Esta tese descreve os estudos desenvolvidos na epidemiologia do vírus West Nile (VWN) em Portugal explorando várias componentes do seu ciclo natural: identificação das populações de mosquitos vetores – distribuição geográfica/ sazonal; análise de determinantes genéticos/ ambientais na preferência de hospedeiro de mosquitos vetores; transmissão experimental do VWN; identificação de flavivírus detectados em mosquitos selvagens; estudo serológico em aves potencialmente reservatórios do vírus; finalmente é descrito um caso clínico humano de infecção por VWN detetado em 2010. Culex pipiens foi uma das espécies de mosquito mais abundantes e demonstrou competência ecológica e intrínseca para transmitir o VWN. Não foram detectados pools de mosquitos positivos para o VWN, mas foram identificados novos flavivírus específicos de insetos. A presença de anticorpos anti-WNV numa rola juvenil sugere circulação local do vírus. Em conclusão, Portugal reúne condições adequadas para a circulação epizoótica do VWN e para a ocorrência de infecções humanas acidentais.